ANALISIS MANAJEMEN WAKTU BELAJAR DALAM MENINGKATKAN KEDISIPLINAN SISWA SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of learning time management in improving the discipline of elementary school students, as well as to identify the efforts and obstacles encountered in the process. The research method used is qualitative with a literature study approach. Data were collected from various sources, including books, scientific journals, and research articles relevant to time management and student discipline. The data collection technique was conducted through content analysis of selected literature systematically and critically. The results of the study indicate that learning time management plays a significant role in shaping students’ discipline. Effective time management helps students organize their study schedules, set priorities, and increase responsibility toward tasks and school rules. Furthermore, efforts to optimize time management include the active role of teachers, consistent habituation, and the creation of a conducive learning environment. However, several obstacles were identified, including low student awareness, lack of parental support, and the negative impact of uncontrolled technology use. Therefore, collaboration among teachers, parents, and the school environment is necessary to support the development of student discipline through effective time management. This study is expected to contribute to the development of learning strategies focused on improving the discipline of elementary school students.